2016
DOI: 10.1785/0120150361
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Seismic‐Hazard Models Prepared for a Seismic Risk Assessment in the Dead Sea Region

Abstract: We derive a probabilistic seismic-hazard model for the Dead Sea region to allow for seismic risk estimation, which will be part of a subsequent study. This hazard model relies as much as possible on data-driven approaches, utilizing a seismic catalog compiled for the region by integrating data from different sources. We derive seismicity models using two different smoothing approaches and estimate a hypocentral depth distribution from historical observations. We do not include paleoseismological evidence apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…These results lead to the conclusion that despite the complex site effects characteristics the earthquake has a major impact on the seismic hazard at a large territorial scale. In this way, it is important to notice that even that we do not include the seismic source parameters as criteria in the MCE analysis (e.g., Erden and Karaman 2012; Giannaraki et al 2019;Haas et al 2016;Mohsen et al 2012), we used the source parameter to estimate the PGA criterion. Our results are consistent with previous work that found that parameters with a large weight have a more critical impact in the seismic hazard at large scale while parameters with a lower weight become more important on smaller scales (e.g., Mohanty et al 2007; Nat and Thingbaijam 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results lead to the conclusion that despite the complex site effects characteristics the earthquake has a major impact on the seismic hazard at a large territorial scale. In this way, it is important to notice that even that we do not include the seismic source parameters as criteria in the MCE analysis (e.g., Erden and Karaman 2012; Giannaraki et al 2019;Haas et al 2016;Mohsen et al 2012), we used the source parameter to estimate the PGA criterion. Our results are consistent with previous work that found that parameters with a large weight have a more critical impact in the seismic hazard at large scale while parameters with a lower weight become more important on smaller scales (e.g., Mohanty et al 2007; Nat and Thingbaijam 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A robust seismic hazard map must be the result of a rigorous computation employing a logic-tree formulation based on all methods explained in this chapter and the combination of several GMPEs [23,[38][39][40], possible maximum magnitudes and slip rates. Besides, it is advisable to check the covariance or the associated error or dispersion of the final results [17,24,25].…”
Section: Vmentioning
confidence: 99%
“…Two recent papers (Al-Tarazi and Sandvol, 2007;Haas et al, 2016) use the gridded-seismicity approach (Frankel, 1995) to produce hazard maps for the entire DST region, based on recorded and historical seismic catalogues, without defining any linear or areal source zones. This approach is becoming more common in areas in which the seismic sources are undefined, or for 10 representation of background seismicity, but is inappropriate for representing large known mapped faults, such as the DST (e.g.…”
Section: Previously Published Hazard Studies In Israelmentioning
confidence: 99%